Analisis Faktor Determinan Minat Mahasiswa memilih Universitas Bina Darma sebagai Perguruan Tinggi di Era Pandemi Covid-19 - Resmiati Putri Anggara; M. Amirudin Syarif (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2022)
Various factors that encourage an increase in student interest in choosing a campus as a place to study, efforts made by universities to attract students to study at Bina Darma University Palembang. The purpose of this study is to analyze the determinants of student interest in choosing Bina Darma University as a university in the era of the Covid-19 pandemic. This research is a field research conducted at Bina Darma University. Sources of data are taken from primary data, namely direct field data and secondary data, namely data from research or other sources. The collection technique is observation, interview method, questionnaire method (questionnaire) and document recording. The population in this study were all students of Bina Darma University. The sample was taken using a random sampling method and set a sample of 100 respondents from Bina Darma University students. The analysis technique carried out in this study uses validity and reliability tests. The next analysis used Multiple Linear Regression Analysis, T test (partial), and F test (simultaneous). The results of the research on the analysis of the determinants of student interest in choosing Bina Darma University as a university in the era of the Covid 19 pandemic, namely there are several factors that influence them, namely personally, psychologically, socially, and culturally.